THE ROLE OF ARCHITECTURE AS A STRESS REDUCER IN THE CAMPUS ENVIRONMENT OF THE FACULTY OF ARCHITECTURE AND DESIGN UPN “VETERAN” JAWA TIMUR - Puspa, Nasywa Anindya; Jasmin, Kamila Jastisia; Manggala, Naremdra; Khairunnisa, Zahrah; Syahbana, Muhammad Thorif Yudha; Harmunisa, Yusvika Ratri (ADBE, 2024)
Stress among students in educational environments is a major problem that reduces their enthusiasm and productivity. Architecture, as a scientific discipline within the field of building planning and design, has the potential to play a role in the design of indoor and outdoor spaces as stress reducers in the campus environment. Efforts to increase the mental resilience of students to reduce stress levels and increase their productivity are being made by designing elements and designs that contribute to a more relaxed and productive campus environment, including spatial layout, colour, furniture and decoration to reduce students’ stress levels. The subject of this research focuses on architecture students at the Faculty of Architecture and Design UPN "Veteran" East Java. The research was conducted to find out the architectural factors that affect the mental health of students in a campus environment that makes their productivity decrease. Knowing the role of architecture itself in creating a comfortable campus environment for students due to the stress of the campus environment is the main objective of this research. The method used is qualitative through observation and interview. The results of this study show that each architectural element in the campus environment affects the atmosphere of the room, and plays an important role as a stress reducer for students.